The Survey of the Use of Video cases in the Pre-service Teacher Education in China (Innovative Teaching and Learning Journal, 2023)
Traditional teacher education overemphasizes know-what and know-about attributes of theories. There is always a disjuncture between theories and practicalities in teaching education. Video case is an effective tool for teacher education to bridge theory and practice. Video cases provide pre-service teachers with early scaffolding for pedagogical preparation in respect of understanding of curriculum, teaching skills, students, and pedagogical uses of course content. This research addressed the importance of video cases and the way of using it in teacher education through combing through literature review and investigated the attitudes of student teachers towards the use of video cases in pre-service teacher education in China. It is found that 37.5% of the respondents claimed that the lack of video cases is the biggest barrier in the development of teaching competence. And the lack of practice (84.4%) and the lack of guidance from the experts (50%) are comparatively more serious than the lack of video cases. Based on the student teachers’ problems and suggestions, a new teacher training model－two cycle video-case based lesson study is proposed to connect theory with practice in the present research. Video-case based lesson study allows the practice to prepare student teachers to become confident and competent novice teachers in the future.
Keywords: video-case; lesson study; video-case based instruction; video-case based lesson study; pre-service English teacher education